Programa de Optimización de Antimicrobianos versus programa convencional en el Hospital de Alta Complejidad “Virgen de la Puerta”, 2015 – 2017 - Peralta Tingal, Ricardo Miguel (2018)
The objective of this report is to evaluate the Antimicrobial Optimization Program (PROA) versus the conventional program at the High Complexity Hospital "Virgen de La Puerta", 2015 - 2017. The consumption was evaluated using DDD/100beds/day of meropenem 500mg imipenem + cilastatin 500mg/125mg in 4 services: Intensive Care Unit (UCI), Intermediate Care Unit (UCIN), Medicine and Infectious Disease, from June 2015 to May 2016 and with PROA from June 2016 to May 2017. Results with the conventional program of meropenem and imipenem + cilastatin were in UCI 25.02 y 21.30; UCIN 18.83 y 14.08; Medicine 10.14 y 14.08 e Infectology con 679 y 7.82 DDD/100beds/day and with PROA in the UCI UCI de 19.04 y 16.90; UCIN de 12.19 y 10.33; Medicine 9.19 y 7.82 e Infectology 6.84 y 4.54DDD/100beds/day respectively. Using the Student T test, the statistical significance was determined with 95% confidence with the conventional program versus the PROA of meropenem and imipenem + cilastatin in the UCI with values of 0.04 and 0.08; UCIN 0.02 and 0.04; Infectology 0.45 and 0.10 and Infectology; 0.02 and 0.04 respectively